(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: A mother who does not breastfeed or unable to breastfeed has a high risk to get breast cancer. Breastfeeding quality in women is influenced by prolactin and oxytocin. The prolactin activates breastmilk production while oxytocin is an important factor in breast milk releasing. Currently, the result of 6-month exclusive breastfeeding program is still below the national target. Therefore, the procedures to assess breastfeeding potential by understanding the hormonal profile should be taken immediately after parturition period. Methods: The study was conducted to 32 first-day postpartum women in the Semarang City Hospital. The sampling method was a purposive sampling. The blood samples were taken 10 hours after postpartum period. The serum analysis used ELISA techniques to measure the oxytocin, prolactin and betaendorphin hormones. Results: The study showed that the breastfeeding mothers are in the age of 15-43 years old. Most of them are working-postpartum-mothers (71.9%). The average oxytocin levels of this sample group is 346 pg/ml, while the average prolactin level in of 245.36 ng/ml, and the average beta-endorphin level is 190.41. There is a correlation between the frequency of breastfeeding with prolactin level (p = 0.001). Moreover, there is also a correlation between breast-milk production with the prolactin (p = 0.005). Similarly, there is a correlation between beta-endorphin hormone with oxytocin (p = 0.000). Conclusion: Breast cancer risk can be reduced through breastfeeding at the age of less 35 years old. Every breastfeeding mother should regularly release breastmilk through breastfeeding as well as milking. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.413-417